2011
DOI: 10.1152/physiolgenomics.00232.2010
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of a subgroup of ribosome-related genes minimizes hypoxia-induced changes and confers hypoxia tolerance

Abstract: Deletion of a subgroup of ribosome-related genes minimizes hypoxia-induced changes and confers hypoxia tolerance. Physiol Genomics 43: 855-872, 2011. First published May 17, 2011 doi:10.1152/physiolgenomics.00232.2010.-Hypoxia is a widely occurring condition experienced by diverse organisms under numerous physiological and disease conditions. To probe the molecular mechanisms underlying hypoxia responses and tolerance, we performed a genome-wide screen to identify mutants with enhanced hypoxia tolerance in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 130 publications
2
8
0
Order By: Relevance
“…In this study, ribosome-related proteins were significantly enriched, which was consistent with the results of earlier research (Shah et al, 2011). Since organisms can conserve energy by suppressing protein synthesis, modifying ribosomal functions is an effective way to minimize hypoxia-induced protein changes and confer hypoxia tolerance (Gerasimovskaya et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…In this study, ribosome-related proteins were significantly enriched, which was consistent with the results of earlier research (Shah et al, 2011). Since organisms can conserve energy by suppressing protein synthesis, modifying ribosomal functions is an effective way to minimize hypoxia-induced protein changes and confer hypoxia tolerance (Gerasimovskaya et al, 2005).…”
Section: Discussionsupporting
confidence: 92%
“…mRNA translation is among the most energy-consuming processes in the cell and the majority of translational regulation occurs at the level of initiation, which is thought to be the rate-limiting step ( 13 , 14 ). It has been shown that protein synthesis has a significant impact on hypoxia tolerance, supporting the pivotal role of mRNA translation in cellular adaptation to hypoxia ( 15 , 16 ). Global suppression of protein synthesis occurs through phosphorylation of the α-subunit of eukaryotic initiation factor 2 (eIF2-α) and inhibition of mammalian target of rapamycin (mTOR) under prolonged hypoxia, both leading to repression of 5â€Č-cap-dependent initiation of mRNA translation ( 17 – 19 ).…”
Section: Introductionmentioning
confidence: 88%
“…Bud21 is also known to be a Ty1 retrotransposon host factor 29 . Deletion of Bud21 renders increased hypoxia tolerance 30 and improved xylose carbon source utilization 31 , while Bud21 expression is upregulated upon acetic acid challenge 32 .…”
Section: Introductionmentioning
confidence: 99%
“…Bud21 is also known to be a Ty1 retrotransposon host factor 29 . Deletion of Bud21 renders increased hypoxia tolerance 30 and improved xylose carbon source utilization 31 , while Bud21 expression is upregulated upon acetic acid challenge 32 . Overall, not much is known about the molecular functions of Utp9 and Bud21 in ribosome biogenesis, even in the well-studied model organism S. cerevisiae .…”
Section: Introductionmentioning
confidence: 99%